THE IMPACTS OF THE COVID-19 PANDEMIC ON THE DEVELOPMENT OF CHILDREN AGED 0 TO 3 YEARS FROM THE PERSPECTIVE OF THE BNCC (BRAZILIAN NATIONAL CURRICULUM BASE) - Pedro, Cleide Martins; de Oliveira, Maria Inês Seredônio (Seven Editora, 2026)
This article analyzes the development of very young children (0 to 3 years old), according to the guidelines of the Brazilian National Common Curricular Base (BNCC), who experienced a period of social distancing due to the COVID-19 pandemic. For approximately two years, these children were deprived of in-person school interactions, which significantly affected their opportunities for social engagement. This situation has often resulted in negative impacts on motor, cognitive, and socio-emotional development, contributing to the intensification of social inequalities. In this context, the study highlights the importance of pedagogical practices in Early Childhood Education as a means of promoting emotional expression and overcoming developmental challenges. Through activities such as drawing, painting, theater, and music, children are able to express feelings, desires, and conflicts, thereby supporting their overall development. Thus, the role of the school is emphasized in providing meaningful experiences that foster learning and strengthen social interactions.